Museums, ethics and cultural heritage / Bernice L Murphy - Murphy, Bernice M.edited by
This volume provides an unparalleled exploration of ethics and museum practice, considering the controversies and debates which surround key issues such as provenance, ownership, cultural identity, environmental sustainability and social engagement. Using a variety of case studies which reflect the internal realities and daily activities of museums as they address these issues, from exhibition content and museum research to education, accountability and new technologies, Museums, Ethics and Cultural Heritage enables a greater understanding of the role of museums as complex and multifaceted institutions of cultural production, identity-formation and heritage preservation.